Evaluasi Program Home Economy Menggunakan Model Context, Input, Process, Product (CIPP) di Sekolah Alam Le Cendekia Boarding School - Mustopa, Ahmad Ali (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to evaluate the Home Economy program at Sekolah Alam Le Cendekia Boarding School using the CIPP (Context, Input, Process, Product) evaluation model. This approach is used to assess various aspects of the program, starting from the relevance of the context, the quality of input, the implementation of the process, to the results achieved. This study uses a descriptive method with a qualitative approach, involving interviews, observations, and document analysis as data collection techniques. The evaluation results show that in terms of context, this program is relevant to the school's vision in shaping student independence. In terms of input, it was found that the facilities and infrastructure were quite adequate, but there was a need for improvement in facilitator training. In terms of process, the implementation of the program mostly went according to plan, although there were challenges in time management. In terms of product, this program succeeded in improving students' practical skills and independence, but ongoing evaluation is needed to ensure the sustainability of its benefits. These findings provide strategic recommendations for the development of the Home Economy program in the future.